2013
DOI: 10.1108/17410391311325234
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of information visibility in two supply chain management information systems

Abstract: PurposeCoordination in supply chains and networks calls for information sharing among the members of the supply chain. Accordingly, information visibility – the availability of relevant information for making supply chain related decisions is an important concept in the context of supply chain management. The purpose of this paper is to identify the different dimensions of information visibility and propose a framework based on these information visibility dimensions. The proposed framework can be used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 63 publications
1
34
0
2
Order By: Relevance
“…There is an assumption that 'competition is no longer between organisations but through their supply chains'. As such, research interest has focused on supply chain performance [6]. For example, a survey of Taiwanese manufacturers, found that supply chain practices have an indirect impact on financial performance [7], whereas a survey of US manufacturers found a strong relationship between supply chain practices and organisational performance [8].…”
Section: Introductionmentioning
confidence: 99%
“…There is an assumption that 'competition is no longer between organisations but through their supply chains'. As such, research interest has focused on supply chain performance [6]. For example, a survey of Taiwanese manufacturers, found that supply chain practices have an indirect impact on financial performance [7], whereas a survey of US manufacturers found a strong relationship between supply chain practices and organisational performance [8].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing level of information sharing among supply chain partners (Albani & Dietz, 2009) and (Goswami et al, 2013). When operational information about key parameters (e.g., inventory level, yield rate) is shared, the customer can establish his own policies in accordance with an acceptance risk level.…”
Section: Methodsmentioning
confidence: 99%
“…In short, companies are now recognizing that their competitive strengths lie not only in their core competencies, but also in their ability to cooperate effectively with business partners. Goswami et al (2013) also examine the need for collaborative information sharing among supply chain partners in terms of information visibility, namely the availability of relevant information for making supply chain decisions. Three dimensions of information visibility are considered -variety, quality and transfer -in a comparative analysis of two supply chain management information systems (SCIS).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations